The role of social entrepreneurship in Malaysia: a preliminary analysis - Mohd Adnan, Raudah; Wan Yusoff, Wan Fauziah; Ghazali, Norliza (American Scientific Publishers, 2018)
Social entrepreneurship involves the application of traditional entrepreneurial principles into context and focuses on social issues. Despite growing rapidly and attracting increased attentions in many developed countries, social entrepreneurship still can be considered new and in fact the activities are still at ground-level within the Malaysian context. This paper provides a review of social entrepreneurship and preliminary analysis of the current state of social entrepreneurship in Malaysia. Specifically, this paper focuses on reviewing the role of social entrepreneurship in enhancing the socio-economics development of the country. Based on the review, it can be concluded that although social entrepreneurship is rather new in Malaysian various agencies whether government or non-government agency begun to realise the importance of social entrepreneurship activities to the social-economic development of the country. Their involvement in various socio-entrepreneurship activities have indirectly contributed to the socio-economic development of the country. It is hoped that the social entrepreneurship continue to grow blossom for future development of the country.